Frasa nomina posesif bahasa Indonesia dalam antologi cerita anak terpilih—Rara dan sepasang sepatu - Suwignyo, Hanum Lintang Siwi (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2024)
Bearing in mind that Indonesian has a D-M word order, making possessive noun phrases— possessiveness in Indonesian cannot be marked with certainty so it cannot be singular-universal. This paper aims to look at the number of words in the BI Possessive FN, the variety of functions in sentences, describe the variations in the BI Possessive FN construct, as well as the relationship between the elements forming the BI Possessive FN found from the data source of the selected children's story anthology Rara and a Pair of Shoes. Data in the form of possessive noun phrases contained in single-compound sentences were analyzed by creating immediate constituents in the form of tree diagrams. Then count the number of words in the Possessive FN, analyze their function and category in the sentence and construct the forming elements in the phrase. The results found that 1) the BI Possessive FN can consist of 2-4 words, 2) the BI Possessive FN occupies the function of subject, object and mandatory-non-obligatory information, and 3) has 6 BI FN constructs, namely a) noun+proper name, b) noun+ kinship word, c) noun+ word of honor or title, d) noun + professional word, e) noun+ personal pronoun, and f) noun+ noun+enclitic 4) contains 4 relationships between its constituent elements, namely a) kinship relationship b) partial relationship overall c) relationship between something and its attributes, and d) locative relationship.